(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Athol Fugard co-wrote the drama Sizwe Banzi is Dead (originally produced and published as Sizwe Bansi is Dead) with two South African actors, John Kani and Winston Ntshona, who both took part in the original performance. The research article focuses on the trauma of African descent people in South Africa caused by a regime from 19240s to early 1990s, known as Apartheid government. It was predominantly created by the minority white people South African government. Sizwe Bansi is Dead being written by Winston Ntshona, John Kani and Athol Fugard Its premier performance was on October 8, 1972 at the Space in Cape Town, South Africa. The main characters Sizwe Bansi played by Winston Ntshona, Styles/Buntu portrayed by John Kani. This play is based on the heartache of identity crises seen by Afro-American community members. By the time apartheid rule came to an end in early 1990, decades earlier this approach had reached its zenith and inequality between South Africa’s white majority and black minority was at its highest level. Blacks was treated as low class citizens and slaves were excluded from all government benefits. These issues are also a major theme of this paper, and the trauma experienced by black people can be connected to their global identity crisis. However, it really seems to go hard on reality with this guy having his own passbook.